2022
DOI: 10.2459/jcm.0000000000001409
|View full text |Cite
|
Sign up to set email alerts
|

Updates in heart failure: sodium glucose co-transporter 2 inhibitors and beyond – major changes are coming

Abstract: Prevalence of heart failure is increasing worldwide mainly due to the ageing of the population and the improvement in diagnosis and treatment. In recent years, huge progress has been made in the management of heart failure patients. A new definition of chronic heart failure based on left ventricular ejection fraction and its possible trajectories has been reported. New drug classes have been introduced for the treatment of chronic heart failure. In particular, the prognostic benefit of sodium glucose co-transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…The burden of HFpEF is increasing worldwide, and patients with HFpEF typically have a poor prognosis. [21][22][23] An accurate prediction of individual patient prognosis may be important to define tailored care strategies (e.g. frequency of clinic visits, home follow-up by healthcare professionals, or prognosis-related discussions with the patient and his/her family members).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burden of HFpEF is increasing worldwide, and patients with HFpEF typically have a poor prognosis. [21][22][23] An accurate prediction of individual patient prognosis may be important to define tailored care strategies (e.g. frequency of clinic visits, home follow-up by healthcare professionals, or prognosis-related discussions with the patient and his/her family members).…”
Section: Discussionmentioning
confidence: 99%
“…The burden of HFpEF is increasing worldwide, and patients with HFpEF typically have a poor prognosis 21–23 . An accurate prediction of individual patient prognosis may be important to define tailored care strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors have been shown to be significant in the treatment of heart failure across the entire spectrum of left ventricular ejection fraction (LVEF), and in particular the prognostic benefit of SGLT2i has been demonstrated for all phenotypes of heart failure. 21 Recent studies demonstrated the results of a reduction in heart failure hospitalizations and cardiovascular fatalities, suggesting that they may have a direct effect on heart failure regardless of their antihyperglycemic properties. When used to treat T2DM, SGLT2 inhibition only slightly decreases hemoglobin A1c while considerably lowering cardiovascular outcomes, indicating that unfavorable cardiovascular events in T2DM are not entirely mediated by dysglycemia.…”
Section: Action Of Sodium-glucose Cotransporter 2 Inhibitors In Heart...mentioning
confidence: 99%
“…In contrast, the most important causes leading to non-ischemic CHF are Myocardial infarction (MI), which is the main cause causing the due to metabolic dysfunction and hypertension [ 1 ]. The prevalence of CHF is continuously increasing, probably due to the parallel increase in aging and the clinical ability to deal with the disease [ 2 ]. The European Society of Cardiology (ESC) highlights two categories of patients based on the left ventricular ejection fraction (LVEF).…”
Section: Introductionmentioning
confidence: 99%